Financial inclusion, financial regulation, and financial education in Thailand - Kanittha Tambunlertchai (Asian Development Bank Institute (ADBI), 2015)
This paper addresses the issue of financial inclusion in Thailand through the lens of an institutional analysis, which takes into consideration the desired outcomes, the service providers and enabling agencies, and the regulatory context that shape the existing provision of financial inclusion in Thailand. In discussing the achievement of the desired outcomes in terms of financial inclusion, the issues of financial education and financial regulation, which provide the contexts within which the provision of financial products and services occur, are also addressed. Using survey information and other evidence, the paper identifies the gaps between desired and existing outcomes, the gap in unmet demand for financial products and services, the gap in financial education provision, and the weakness of the existing regulatory institutional setting. The paper concludes with policy recommendations for achieving the desired outcomes in terms of financial inclusion within the context of Thailand.
Keywords: G21; G28; O16; 330